DIPLOMASI BUDAYA KOREA SELATAN TERHADAP INDONESIA STUDI KASUS : SM Entertainment Sebagai Aktor Non Negara Dalam Mempromosikan Kebudayaan K-POP DI Indonesia - Muhammad Mulyanda Fazry (2022)
This study talks about South Korean cultural diplomacy introducing K-Pop culture through SM Enterainment as the actor who is part of the country's soft power in Indonesia. This study uses the concepts of cultural diplomacy and nation branding or state image, plus the use of qualitative methods (case studies) with explorative research types in the analysis process. From this research, it was found that the cultural diplomacy carried out by South Korea through SM Entertainment in Indonesia was pursued through three forms of activity, namely exhibition, negotiation and penetration as well as various fields such as talent management, visual content production, event production, promotion, advertising, merchandising, and a mobile platform in collaboration with Trans Media. In addition, this activity can also help South Korea in its efforts to gain profits, seen from the many achievements in Indonesia, such as increasing cultural promotion, improving the country's image, and increasing Indonesia's interest in this culture.